Surgical Management of Skull Base Osteoradionecrosis in the Cancer Population – Treatment Outcomes and Predictors of Recurrence: A Case Series. Issue 4 (23rd April 2020) - Habib, Ahmed; Hanasono, Matthew M; DeMonte, Franco; Haider, Ali; Breshears, Jonathan D; Nader, Marc-Elie; Gidley, Paul W; Su, Shirley Y; Hanna, Ehab Y; Raza, Shaan M
Abstract: BACKGROUND: Skull base osteoradionecrosis (ORN) is a challenging treatment-related complication sometimes seen in patients with cancer. Although ORN management strategies for other anatomic sites have been reported, there is a paucity of data guiding the management of skull base ORN. OBJECTIVE: To report a single-center tertiary care series of skull base ORN and to better understand the factors affecting ORN recurrence after surgical management. METHODS: We conducted a retrospective cohort study of patients with skull base ORN treated at our center between 2003 and 2017. Univariate and multivariate binary logistic regressions were performed to identify predictors of recurrence. RESULTS: A total of 31 patients were included in this study. The median age at ORN diagnosis was 61.1 yr (range, 32.8-84.9 yr). Of these 31 patients, 15 (48.4%) patients were initially treated medically. All 31 patients underwent surgery. Three (14.3%) of 21 patients treated with a free flap and 4 (50.0%) of 8 patients who underwent primary closure experienced recurrence. Cox regression analysis revealed that reconstruction with local tissue closure (P  = .044) and ongoing treatment for active primary cancer ( P  = .022) were significant predictors of recurrence. The median overall survival from index surgery for ORN treatment was 83.9 mo. At 12-mo follow-up, 78.5% of patients were alive. CONCLUSION: In this study, we assess the outcomes of our treatment approach, surgical debridement with vascularized reconstruction, on recurrence-free survival in patients with skull base ORN. Further studies with larger cohorts are needed to assess current treatment paradigms. Graphical Abstract: